Students achievement in mathematics: the relationship between performance in Calculus I and Calculus II / Maisurah Shamsuddin, Siti Balqis Mahlan and Norazah Umar - Shamsuddin, Maisurah; Mahlan, Siti Balqis; Umar, Norazah (UiTM Cawangan Perlis, 2025)
Calculus is among the most important branches of mathematics that is widely used in various fields of science and engineering. It explores changes using basic ideas, including integration, differentiation and limitation. The goal of advanced calculus is to take the basic ideas of calculus to a deeper and more complex level. Basic and advanced calculus have a supportive relationship where learning increasingly difficult problems in advanced calculus requires a solid understanding of basic calculus concepts. Therefore, this study attempts to determine whether the assessment results of engineering students for the subjects calculus I (basic) and calculus II (advanced) have a significant relationship with each other. In addition, student performance in these two subjects was descriptively evaluated. The research sample used was a total of 67 Engineering students who took Calculus I (March - August 23 semesters) and Calculus II (October 23 - February 24 semesters). Students' final assessment scores were taken and analysed using SPSS version 2.0 software through descriptive statistics and Person correlation. Results showed that the performance of students who obtained an A grade in Calculus II had increased by 10% from Calculus I. Based on the Person Correlation analysis, there was a strong positive linear relationship between Calculus I and II with a value of r=0.561 (p-value < 0.05). Although this relationship was significant, only 32.6% of the variation in Calculus II can be explained in this model. It suggests that a wide range of other factors, including learning and teaching strategies used by lecturers or by students themselves, can have an impact on students' performance. Since understanding engineering mathematics necessitates a solid calculus foundation, it is hoped that this study will encourage students to work hard at improving their grasp of the fundamentals of the subject